PENGARUH TOTAL PEMBIAYAAN, NPF, DAN BOPO TERHADAP LABA BANK UMUM SYARIAH PERIODE 2019-2023 - Matondang, Nurhaliza; Meiria, Endah (Bina Ekonomi, 2025)
The increase in profits is one of the factors to strengthen the market share position of Islamic banks. The increase in profit depends on the bank's activities themselves, both from financing which is the main source of income for the bank and from its operational implementation. The purpose of this study is to be able to know the effect of total financing, Non Performing Financing (NPF), and operational efficiency (BOPO) on the net profit of the Sharia General Bank (BUS). Data analysis was in the form of panel data regression analysis using annual data 2019-2023 using 6 BUS samples through purposive sampling techniques. The results shown through this study are that partially total financing has a positive influence while NPF and BOPO have a negative effect on net profit. Simultaneously, this study shows that total financing, NPF, and BOPO affect the net profit of Sharia Commercial Banks..